Molecular Detection of some Virulence Genes of Streptococcus agalactiae Isolated from Pregnant Women - Lamees A. Abdul-Lateef (Journal of Global Pharma Technology, 2019)
virulence factors like surface proteins, biofilm, and exotoxins s. All these allow bacteria to adhere to tissues causing pathogenesis and invade the immune system causing serious infection. Materials and Methods: A total of 300 samples, 25 of Strep. Agalactiae were collected in this study. Strep. Agalactiae were isolated from pregnant women by standard bacteriological methods. PCR was conducted to determine the some virulence genes of the isolates by using primers cyle, scpB, and hylB. The PCR amplification products were visualized by electrophoresis on 1% agarose gels for 30min at 70v. The size of the amplicons was determined by comparison to the 100 bp allelic ladder. Results: In this study, 25 isolates of Strep. agalactiae were genotypically characterized by PCR assay. Among isolates studies it was found that cylE gene present in all isolates. Also 100% of isolates have ability to produce scpB gene while only 11(44%) was able to produce hylB.Keywords: Streptococcus agalactiae, cylE, scpB, hylB.